DIYAT SSEBAGAI PENGGANTI QISHAS PADA JARIMAH PEMBUNUHAN SEBAB PEMAAFAN - ihsan, muhammad (LEGALITE, 2016)
The punishment for the perpetrator of murder is not always required qishas, but it can be done with the payment of Diyat in exchange for the Qishas punishment, in some provisions even the victims?s heir is given the right to choose between Qishas or aplogize. Giving forgiveness is the closest heir of the victim such as husband / wife, father, mother, and child (male / female), and also brothers (male / female), uncle, aunt. The consideration of  forgiveness is the motivation to gain rewards, alms, penance, the way to taqwa, forgiveness is one of God's commands. The Apology is filed by the murderer himself or his family, it is asked to the guardian of the murder victim. If the family?s victim decides to apologize the murderer, the offender must pay Diyat in accordance with Islamic Law provision.